If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(x + -2)(x + 1)(x + 2) = 84 Reorder the terms: (-3 + x)(x + -2)(x + 1)(x + 2) = 84 Reorder the terms: (-3 + x)(-2 + x)(x + 1)(x + 2) = 84 Reorder the terms: (-3 + x)(-2 + x)(1 + x)(x + 2) = 84 Reorder the terms: (-3 + x)(-2 + x)(1 + x)(2 + x) = 84 Multiply (-3 + x) * (-2 + x) (-3(-2 + x) + x(-2 + x))(1 + x)(2 + x) = 84 ((-2 * -3 + x * -3) + x(-2 + x))(1 + x)(2 + x) = 84 ((6 + -3x) + x(-2 + x))(1 + x)(2 + x) = 84 (6 + -3x + (-2 * x + x * x))(1 + x)(2 + x) = 84 (6 + -3x + (-2x + x2))(1 + x)(2 + x) = 84 Combine like terms: -3x + -2x = -5x (6 + -5x + x2)(1 + x)(2 + x) = 84 Multiply (6 + -5x + x2) * (1 + x) (6(1 + x) + -5x * (1 + x) + x2(1 + x))(2 + x) = 84 ((1 * 6 + x * 6) + -5x * (1 + x) + x2(1 + x))(2 + x) = 84 ((6 + 6x) + -5x * (1 + x) + x2(1 + x))(2 + x) = 84 (6 + 6x + (1 * -5x + x * -5x) + x2(1 + x))(2 + x) = 84 (6 + 6x + (-5x + -5x2) + x2(1 + x))(2 + x) = 84 (6 + 6x + -5x + -5x2 + (1 * x2 + x * x2))(2 + x) = 84 (6 + 6x + -5x + -5x2 + (1x2 + x3))(2 + x) = 84 Combine like terms: 6x + -5x = 1x (6 + 1x + -5x2 + 1x2 + x3)(2 + x) = 84 Combine like terms: -5x2 + 1x2 = -4x2 (6 + 1x + -4x2 + x3)(2 + x) = 84 Multiply (6 + 1x + -4x2 + x3) * (2 + x) (6(2 + x) + 1x * (2 + x) + -4x2 * (2 + x) + x3(2 + x)) = 84 ((2 * 6 + x * 6) + 1x * (2 + x) + -4x2 * (2 + x) + x3(2 + x)) = 84 ((12 + 6x) + 1x * (2 + x) + -4x2 * (2 + x) + x3(2 + x)) = 84 (12 + 6x + (2 * 1x + x * 1x) + -4x2 * (2 + x) + x3(2 + x)) = 84 (12 + 6x + (2x + 1x2) + -4x2 * (2 + x) + x3(2 + x)) = 84 (12 + 6x + 2x + 1x2 + (2 * -4x2 + x * -4x2) + x3(2 + x)) = 84 (12 + 6x + 2x + 1x2 + (-8x2 + -4x3) + x3(2 + x)) = 84 (12 + 6x + 2x + 1x2 + -8x2 + -4x3 + (2 * x3 + x * x3)) = 84 (12 + 6x + 2x + 1x2 + -8x2 + -4x3 + (2x3 + x4)) = 84 Combine like terms: 6x + 2x = 8x (12 + 8x + 1x2 + -8x2 + -4x3 + 2x3 + x4) = 84 Combine like terms: 1x2 + -8x2 = -7x2 (12 + 8x + -7x2 + -4x3 + 2x3 + x4) = 84 Combine like terms: -4x3 + 2x3 = -2x3 (12 + 8x + -7x2 + -2x3 + x4) = 84 Solving 12 + 8x + -7x2 + -2x3 + x4 = 84 Solving for variable 'x'. Reorder the terms: 12 + -84 + 8x + -7x2 + -2x3 + x4 = 84 + -84 Combine like terms: 12 + -84 = -72 -72 + 8x + -7x2 + -2x3 + x4 = 84 + -84 Combine like terms: 84 + -84 = 0 -72 + 8x + -7x2 + -2x3 + x4 = 0 The solution to this equation could not be determined.
| 3(w+4)=-2(1.5-6) | | 3m+2=0 | | 3x-6+4x=-41 | | 2n+3=12n+2 | | 6b+11=29 | | 4(r-3)=-3(r+2) | | 4x+3+2x=18 | | 6+4x+2=-9-3x+3 | | 5(8)+a= | | -7(2x-x)=x | | 5(x-4)=-4x+79 | | 23(d+5)=529 | | x+33=x*5+13 | | 30+6r=180 | | 12(2x+5)=126 | | 9-4x+3=7+2x-13 | | 1x-4+x=9 | | 14(p-915)=798 | | z^4+4i=0 | | a^2+b^2=3.8729833462074 | | 11(5x-12)=110x | | 2w^2-w-13=2 | | 2x-(x-4)=0 | | 9[x-9]=72 | | (7-2x)-(4+x)= | | 4d^2-8=d | | a^2+9a=10 | | 9w^2-11=6w | | c=39.62+0.25x | | x*x-4=1 | | 5sin^2x-7cos+1=0 | | 4+2x-6x=7-3x-4 |